2004
DOI: 10.2165/00002018-200427050-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Xyrem?? Risk Management Program

Abstract: Sodium oxybate, also known as gamma-hydroxybutyric acid (GHB), was discovered in 1960 and has been described both as a therapeutic agent with high medical value and, more recently, a substance of abuse. The naturally occurring form of this drug is found in various body tissues but has been studied most extensively in the CNS where its possible function as a neurotransmitter continues to be studied. Sodium oxybate has been approved in different countries for such varied uses as general anaesthesia, the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 26 publications
0
41
0
1
Order By: Relevance
“…Although it has been abandoned as anaesthetic agent in most countries because of side effects such as seizures and coma, it is still registered in Germany (Somsanit®). The sodium salt of GHB, known under the international drug name sodium oxybate, has a role in the treatment of narcolepsy with cataplexy (Xyrem®) and of opiate and alcohol withdrawal (Alcover®) [7][8][9][10][11].…”
Section: Troductiomentioning
confidence: 99%
“…Although it has been abandoned as anaesthetic agent in most countries because of side effects such as seizures and coma, it is still registered in Germany (Somsanit®). The sodium salt of GHB, known under the international drug name sodium oxybate, has a role in the treatment of narcolepsy with cataplexy (Xyrem®) and of opiate and alcohol withdrawal (Alcover®) [7][8][9][10][11].…”
Section: Troductiomentioning
confidence: 99%
“…39 Abuse, addiction, withdrawal syndrome, and overdoses have been documented with GHB, which led to its 1990's ban and placement as a Schedule I agent under the Controlled Substances Act. 40,41 Concerns regarding the history of abuse of GHB were taken into consideration by the Food and Drug Administration (FDA) and the manufacturer in the development of sodium oxybate. 40,41 Sodium oxybate (γ-hydroxybutyrate; Xyrem ® ) was approved in 2002 by the Food and Drug Administration as an orphan drug for the management of narcolepsy.…”
Section: Sodium Oxybatementioning
confidence: 99%
“…It has been demonstrated that GHB administration in narcoleptic patients with cataplexy increases slow-wave sleep duration, improves EDS and reduces the number of awakenings at night. [4][5][6] Therefore, sodium oxybate has been approved in 2002 by the US Food and Drug Administration (FDA) for the treatment of cataplexy in narcolepsy patients, and subsequently in 2005 for the treatment of EDS in narcolepsy patients. Also, in 2005, the European Medicines Agency (EMA) approved sodium oxybate for the treatment of narcolepsy with cataplexy.…”
Section: Introductionmentioning
confidence: 99%
“…The first dose should be taken at bedtime and the second 2.5-4 h later. [4][5][6] Intraand interindividual variation in clinical effect has been seen with sodium oxybate; however, it is not known whether this correlates with variation in obtained GHB concentrations. Therefore, the dried blood spot (DBS) sampling technique, stated to be easy and minimally invasive, may be useful to obtain patient samples in a non-hospital-based setting.…”
Section: Introductionmentioning
confidence: 99%